Business Analysis of Palm Sap Products in Binawidya District Pekanbaru - Evi Sribudiani; Eka Indra Setiawan; Mukhamadun; Pebriandi (Jurnal Ilmu Ilmu Kehutanan, 2024)
Palm sap is a liquid produced from palm flower threads. Dates juice can be made into drinks, and sugar, liquid sugar, and block sugar. Many coffee shop companies use sap products and the business feasibility of selling sap products is unknown. This study aims to analyze the feasibility of the juice product business in Binawidya District, Pekanbaru City. Data collection uses observation methods, in-depth interviews, and library research. Sampling by census method. Data analysis was performed with quantitative descriptive analysis. The results of the study show that the total turnover of day shops and coffee shops exceeds the total costs of business actors. The total revenue that is greater than the total cost indicates that the palm juice product business is profitable. The largest total income earned is the coffee shop business with a nominal value of Rp. 46,115,003/mount. The level of income at the coffee shop is influenced by the service of processed palm juice products. The results of the R/C analysis of palm sap product companies in Binawidya District, Pekanbaru City, obtained for each sap product company is R/C ratio > 1, which means the company is profitable and the company is feasible to work on.